The Effect of Product Quality and Service Quality on Customer Loyalty at PT Asuransi Candi Utama Mediated by Customer Satisfaction - Puji Lestari; Imam Wibowo; Saoloan Samosir, Partogi (Madani Connection, 2025)
This study aims to: 1) examine the effect of product quality on customer satisfaction, 2) examine the effect of service quality on customer satisfaction, 3) examine the effect of product quality on customer loyalty, 4) examine the effect of service quality on customer loyalty, 5) examine the effect of customer satisfaction on customer loyalty, 6) examine the effect of product quality on customer loyalty through customer satisfaction, and 7) examine the effect of service quality on customer loyalty through customer satisfaction. The research was conducted at PT Asuransi Candi Utama with a sample of 92 respondents selected using incidental sampling technique. Data analysis methods include descriptive analysis and path analysis. The results show that: 1) product quality has an effect on customer satisfaction, 2) service quality has an effect on customer satisfaction, 3) product quality has an effect on customer loyalty, 4) service quality has an effect on customer loyalty, 5) customer satisfaction has an effect on customer loyalty, 6) product quality has no effect on customer loyalty through customer satisfaction, and 7) service quality has no effect on customer loyalty through customer satisfaction. Customer satisfaction does not mediate the relationship between product quality and service quality on customer loyalty. These findings imply that in the context of the insurance industry, strengthening product and service quality remains a key factor in building customer loyalty, even though satisfaction has not been proven to be a significant mediator.